POINT-CONTERPOINT: METODE DEBAT DALAM PROSES PEMBELAJARAN DAN PENGARUHNYA TERHADAP MAHASISWA DI ACEH - Sri Astuti A. Samad; Abidin Nurdin; Munawwarah Samad; Herawati (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
This article discusses the point-counterpoint method, or debating, in the learning process and its impact on students in Aceh. This study is a qualitative study using descriptive analysis. The debating method is crucial in the learning process because it can determine the success or failure of the learning carried out by lecturers, teachers, and educators. This article concludes that the method of debating opinions in the learning process is carried out by discussing a problem to find the best answer, not looking for who loses. The benefits of the debate method with students, namely increasing thinking power, being active in the learning process, respecting the opinions of others, and being able to work together in groups. Philosophically, using the debate method in the learning process, students will experience cognitive and affective intelligence. Because debating the ability to analyze thoughts, provide arguments and respect for the opinions of others, and express ideas in a polite manner occurs in the learning process the debate of opinion takes place.